Spectroelectrochemical studies of the redox active tris[4-(triazol-1-yl)phenyl]amine linker and redox state manipulation of Mn(ii)/Cu(ii) coordination frameworks. Issue 27 (10th June 2019) - Ngue, Chin-May; Liu, Yen-Hsiang; Wen, Yuh-Sheng; Leung, Man-Kit; Chiu, Ching-Wen; Lu, Kuang-Lieh
Abstract : In situ spectroelectrochemical methods were conducted to investigate the redox active tris(4-(1 H -1, 2, 4-triazol-1-yl)phenyl)amine (TTPA) ligand and its incorporation into the solid state of Mn(ii ) and Cu(ii ) frameworks. Abstract : This work describes the successful incorporation of a redox active linker, tris(4-(1 H -1, 2, 4-triazol-1-yl)phenyl)amine (TTPA) into Mn(ii )/Cu(ii ) based coordination frameworks. Solution state in situ spectroelectrochemistry of EPR and UV/Vis/NIR of the TTPA ligand were measured to gain a deeper understanding of the charge delocalization of the triphenylamine backbone. The assignments of the absorption bands for the radical cations in UV/Vis/NIR spectroelectrochemistry were supported by DFT calculations. For Mn(ii )/Cu(ii ) based coordination frameworks, solid state electrochemical and in situ spectroelectrochemical methods were applied to elucidate the accessible redox states and the optical properties of the frameworks. The findings provide a basic comprehension of the interconversion of different redox states and how an electroactive framework can be potentially used in applications of electrochromic and optical devices.